2008
DOI: 10.1111/j.1464-5491.2008.02487.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diabetes mellitus on the prevalence of rheumatoid arthritis: a case–control study

Abstract: References1 Bansal S, Buring JE, Rifai N, Mora S, Sacks FM, Ridker PM. Fasting compared with non-fasting triglycerides and risk of cardiovascular events in women. J Am Med Assoc 2007; 298: 309-316. 2 Nordestgaard BG, Benn M, Schnohr P, Tybjaerg-Hansen A. Nonfasting triglycerides and risk of myocardial infarction, ischemic heart disease, and death in men and women. J Am Med Assoc 2007; 298: 299-308. 3 Oka R, Hifumi S, Kobayashi J, Mabuchi H, Asano A, Yagi K et al. The relationship between postprandial plasma gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Tentolouris et al tested the hypothesis that patients with pre-existing DM might have a lower RA prevalence than the general population because of immunosuppression associated with DM 44. Although their study results did not prove their hypothesis, they suggested that it may easily reach statistical significance when the number of patients with type 2 DM increased to 1500 44. Clearly, additional cohort studies are warranted to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Tentolouris et al tested the hypothesis that patients with pre-existing DM might have a lower RA prevalence than the general population because of immunosuppression associated with DM 44. Although their study results did not prove their hypothesis, they suggested that it may easily reach statistical significance when the number of patients with type 2 DM increased to 1500 44. Clearly, additional cohort studies are warranted to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above we examined previously the hypothesis that pre-existing hyperglycemia may have a protective effect on the development of RA (11), a disease in which the earliest event is an intense inflammatory response to unknown stimuli within the joint. In a preliminary study we found that in patients with type 1 DM (T1DM), which coexists with other autoimmune diseases including RA (12), the prevalence of RA was higher in patients with T1DM compared with age-and gender-matched controls without DM (0.58% vs. 0.39%, respectively) (11). In contrast, RA prevalence was lower in patients with type 2 DM (T2DM) (0.25% vs. 0.83% in controls), albeit the difference did not reach statistical significance (11).…”
Section: R H E U M a T O I D A R T H R I T I S ( R A ) I S T H E M O mentioning
confidence: 99%
“…In a preliminary study we found that in patients with type 1 DM (T1DM), which coexists with other autoimmune diseases including RA (12), the prevalence of RA was higher in patients with T1DM compared with age-and gender-matched controls without DM (0.58% vs. 0.39%, respectively) (11). In contrast, RA prevalence was lower in patients with type 2 DM (T2DM) (0.25% vs. 0.83% in controls), albeit the difference did not reach statistical significance (11). Apart from our study, there are a few previous studies that have examined the relationship between DM and RA with conflicting results (13)(14)(15).…”
Section: R H E U M a T O I D A R T H R I T I S ( R A ) I S T H E M O mentioning
confidence: 99%
“…We also found a similar protective effect of treated DM on RA risk in our previous study [ 24 ]. Possible explanations included an immunosuppressive effect by hyperglycemia [ 32 ], or possible immunomodulatory effects of some anti-diabetic drugs [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%